2003
DOI: 10.3346/jkms.2003.18.5.655
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induced Acute Lung Injury and TUNEL Expression of Apoptosis in Respiratory Cells

Abstract: We examined the ultrastructural features of the lung parenchyma and the expression of apoptosis of the respiratory cells by TUNEL technique. Male Sprague-Dawley rats (n=30) were intra-tracheally injected with cadmium (2.5 mg/kg) into both lungs. The light and electron microscopic features of the lung tissues were examined on Days 1, 3, 7 and 10 after the injection of cadmium. Specimen preparations for the light and electron microscopic TUNEL stains were performed. Ultrastructurally, on Days 1 and 3, the alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
8
8
0
Order By: Relevance
“…Analysis of tumor genesis revealed that death resistance capacity can be acquired by different mechanisms, how contact with external soluble factors, especially carcinogenic agents 16 . Similar results were observed by Kwon et al 17 after intra-tracheal injection of cadmium into both rats lungs. Authors observed a time-response decrease of apoptotic cells 17 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Analysis of tumor genesis revealed that death resistance capacity can be acquired by different mechanisms, how contact with external soluble factors, especially carcinogenic agents 16 . Similar results were observed by Kwon et al 17 after intra-tracheal injection of cadmium into both rats lungs. Authors observed a time-response decrease of apoptotic cells 17 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were observed by Kwon et al 17 after intra-tracheal injection of cadmium into both rats lungs. Authors observed a time-response decrease of apoptotic cells 17 .…”
Section: Discussionsupporting
confidence: 91%
“…The action of metals, such as Cd and Pb, can deteriorate DNA and originate cancer, yet the same metals can also initiate the process of apoptosis capable of eliminating cells with damaged DNA and this way prevent cancer (Singh et al 1999). From the four metals taken into account, Cd is one of the most toxic and the one that recognizably induces apoptosis in cells from different organs (Hamada et al 1997;Habeebu et al 1998;Wätjen and Beyersmann 2004), and is capable of causing this type of cellular death in the lung (Lag et al 2002) even at 2.5 mg/kg (Kwon et al 2003), i.e. at levels well below the ones found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In mice from Rabo de Peixe, the lung presented levels of Pb higher than those from Furnas, that may be justified by the proximity of that sampling area to a site where extraction of basaltic rock and aggregate production occurs, this way contributing with dusts produced during the separation and transformation of basalt rich in Pb (Drever 1997) that can be retained, in part, in the respiratory tract but also in the lung. Cd and Pb, on their own or in mixtures, besides being able to cause the diminishment of ciliated bronchial cells, which are responsible by the secretion of pulmonary surfactants necessary to protect the bronchi (Fortoul et al 2004(Fortoul et al , 2005, can also cause either apoptosis or lung cancer (Singh et al 1999;Kwon et al 2003). In spite of the few known harmful effects of Al over biologic systems, it is recognized its preferential accumulation in the lung, where it can originate fibrosis and granulomatosis when in high concentrations (Agency for Toxic Substances and Disease Registry 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cd compounds are classified as human carcinogens by several regulatory agencies (Hossain et al, 2002;Mahalik et al, 1995;Satarug et al, 2004;Sunderman, 2001). The most convincing data that Cd is carcinogenic for humans result from studies that state that occupational Cd exposure is associated with lung cancer (Kwon et al, 2003;Lagorio et al, 2006;Persson et al, 2003). Cd exposure has also been linked to human prostate and renal cancer, although this relationship is weaker than for lung cancer (Waalkes, 2003).…”
mentioning
confidence: 97%